POPULATION DYNAMICS OF METAZOAN PARASITES OF PACIFIC GUITAR FISH RHINOBATOS PLANICEPS (BATOIDEA: RAJIFORMES) OF THE COASTAL MARINE ZONE OF LIMA, PERU - Iannacone, José (2011)
Thirty-six specimens of Rhinobatos planiceps (Garman, 1880) "Pacific guitar fish" were acquired from the Chorrillos Fishmarket, Lima, Peru between September 2009 and August 2010 to assess the population dynamics of parasitic metazoa. Of the fish examined, 14 were females and 22 were males. The fish had an average total length of 85.0 ± 19.3 cm (27 to 125). Metazoan parasites were collected and counted using standard parasitological protocols. The parasite assemblage recorded a higher percentage of endoparasites than ectoparasites. All hosts showed infection with at least one parasitic species. Ten species were found with the following prevalence of infection and mean abundance: three species of Monogenea: Anoplocotyloides papillatus (41.6% and 1.1), A. chorrillensis (30.5% and 0.5) and Rhinobatonchocotyle pacifica (63.8% and 4.1), three species of cestodes: Rhinebothrium rhinobati (8.3% and 0.1), Prochristianella heteracantha (11.1% and 0 , 1) and Acanthobothrium olseni (27.7% and 0.6), one nematode Proleptus carvajali (80.5% and 148), one hirudinean Stibarobdella moorei (5.5% and 0.1), and finally two species of copepods Eudactylina peruensis (2.7% and 0.02) and Ommatokoita elongata (13.8% and 0.2). The specific importance index showed that P. carvajali presented the highest value and is considered a core species in the parasite community. The total length was not related to the prevalence and abundance of parasitic infection, except for a negative relationship with the prevalence of the copepod O. elongata. A differential pattern in the mean abundance of infection between parasitized and unparasitized fish with A. papillatus and R. pacifica was observed. The interactivity indexes (CC ) for ectoparasites (29.9%) and endoparasites (32.8%) of R. planiceps 50 show that communities are interactive.